Combined 34S, 33S and 18O isotope fractionations record different intracellular steps of microbial sulfate reduction. (15th April 2017) - Antler, Gilad; Turchyn, Alexandra V.; Ono, Shuhei; Sivan, Orit; Bosak, Tanja
Abstract: Several enzymatic steps in microbial sulfate reduction (MSR) fractionate the isotope ratios of 33 S/ 32 S, 34 S/ 32 S and 18 O/ 16 O in extracellular sulfate, but the effects of different intracellular processes on the isotopic composition of residual sulfate are still not well quantified. We measured combined multiple sulfur ( 33 S/ 32 S, 34 S/ 32 S) and oxygen ( 18 O/ 16 O) isotope ratios of sulfate in pure cultures of a marine sulfate reducing bacterium Desulfovibrio sp. DMSS-1 grown on different organic substrates. These measurements are consistent with the previously reported correlations of oxygen and sulfur isotope fractionations with the cell-specific rate of MSR: faster reduction rates produced smaller isotopic fractionations for all isotopes. Combined isotope fractionation of oxygen and multiple sulfur isotopes are also consistent with the relationship between the rate limiting step during microbial sulfate reduction and the availability of the DsrC subunit. These experiments help reconstruct and interpret processes that operate in natural pore waters characterized by high 18 O/ 16 O and moderate 34 S/ 32 S ratios and suggest that some multiple isotope signals in the environment cannot be explained by microbial sulfate reduction alone. Instead, these signals support the presence of active, but slow sulfate reduction as well as the reoxidation of sulfide.